HBsAg in Cord Blood Qf Newborns of HBsAg-Positive Mothers - Adnan S. Wiharta; Evi Setiadi; H. M. Sjaifullah Noer; Triyatmo Rachimhadhi; Asri Rasad (Indonesian Pediatric Society, 1994)
Vertical transmission of hepatitis B infection that may occur during pregnancy at delivery-, in infancy, and early childhood has an important role in the development of chronic hepatitis B. Intrauterine infection is suspected to occur when hepatitis B viruses cross the placenta into fetal circulation due to failure of placental tissue function. In Cipto Mangunkusumo Hospital, Jakarta, 98 (6.4%) of 1536 pregnant mothers obseiVed during 3 years (1987 -1990) showed positive HBsAg. Six (8.3%) of 60 babies of born to HBsAg positive mothers showed positive HBsAg in their cord blood, but this disappeared after one month. All babies born to HBsAg positive mothers were vaccinated on months 0, 1, 2, and 12. HBsAg in cord blood might not play an important role in vertical transmission.